(untitled) (Acta Scientiarum. Technology, 2017)
This paper aims to present a study on the implantation of design methods in the Product Development Process (PDP) of companies, with the intention of generating a set of decision support principles and recommendations for deployment of these resources in the industry. This study was classified as applied research, as it aims to apply knowledge in industry´s product development. On the approach, it was classified as a qualitative research because it used interviews, document examinations and has a descriptive character. As for the goals, it was classified as exploratory and descriptive, having a practical application. The technical procedures used were literature review, field study and action research. The main result of this research is a group of systematic character propositions that are the foundation to guide the implementation of design methods in the industry, consisting of Selecting the Appropriate method to be implemented in accordance with PDP, Planning the Implantation of the method selected, Applying the Method and control and actions to improve the implementation. The research offers a synthesis of various experiences about the implantation of design methods in the industry, redeeming values of human wisdom that previously had not received great attention. Â